Direito eleitoral brasileiro à luz da democracia deliberativa: uma análise crítica em perspectiva hermenêutica - Ferraz, Ricardo de Barros Falcão (Universidade do Vale do Rio dos Sinos, 2018)
The present thesis aims to propose a critical analysis in phenomenological-hermeneutic perspective of the potential contribution of the Electoral Justice to the development of Brazilian democracy. In question, the dogmatic deep link of the Electoral Law is placed to the normative contours conferred to the representative system. And, based on the premise that the historically experienced democratic models are partially overcome, we question the institutional mismatch with the transformative impact of the political culture developed by a culturally changing individuality. On the one hand, backed by the functionalist theory of political culture, it aims to demonstrate the phenomenal contribution of Electoral law in the process of culture formation; on the other, from the perspective of the individualist methodology, the continuous reconfiguration of the traditional channels of articulation and deliberative aggregation of interests promoted in the scope of political communication. As a dialogical result, political self-determination is experienced, operationalized through the principles of full freedom and self-restraint, individualist deliberative characteristics highlighted in the current phase of Brazilian democracy, as the main structures that inform the cultural re-signification of the functions and attributions exercised by the institutions of the Electoral Law, among which the Electoral Court rises above the others.
Keywords: Democracia; Democracia deliberativa; Liberdade plena; Autocontenção; Direito eleitoral; Justiça eleitoral; Democracy; Deliberative democracy; Full freedom; Self-containment; Electoral law; Electoral justice; ACCNPQ::Ciências Sociais Aplicadas::Direito